Flow-induced structures observed in a viscoelastic reverse wormlike micellar system by magnetic resonance imaging and NMR velocimetry. Issue 40 (6th April 2016) - Angelico, R.; Gentile, L.; Ranieri, G. A.; Oliviero Rossi, C.
Abstract : Organogel formed by lecithin reverse wormlike micelles in the isotropic concentrated regime exhibits flow induced micro-heterogeneities detected by rheo-NMR and NMR-velocimetry. Abstract : The aim of the present work is to illustrate and discuss an application of rheo-NMR techniques in the investigation of the flow micro-morphology of a rheo-thinning fluid. The viscoelastic material is composed by weakly hydrated nonionic Wormlike Micelles (WM), stabilized by the biocompatible phospholipid in an organic solvent (lecithin organogel). By applying rheo-NMR techniques, such as micro-imaging and flow velocimetry in Couette flow, to lecithin organogels in the concentrated isotropic phase, a new phase nucleating inhomogeneously at the inner rotating cylinder showing periodic fluctuations in space in some cases, has been identified for applied shear rates within the isotropic-nematic stress plateau. On the other hand, evident slippage phenomena have been found in flow regimes consistent with a full shear-induced nematic state. Bulk rheometric investigations executed in oscillatory, steady state and transient mode have been finally carried out to bridge different flow micro-heterogeneities detected by rheo-NMR with a variety of mechanical responses manifested by lecithin WM.